2017
DOI: 10.4236/cus.2017.54024
|View full text |Cite
|
Sign up to set email alerts
|

Redistribution, Growth, and Inclusion: The Development of the Urban Housing System in China, 1949-2015

Abstract: This paper explains the development of the urban housing system in China from 1949 to 2011 with an emphasis on the factors driving housing inequality in each policy period. We argue that the logic underpinning the housing policy had shifted from socialist redistribution to the stimulation of growth in the process of market economy reform and has been shifting toward social inclusionary growth since the 2010s. Over the course of time, two institutional factors (work units and household registration/hukou) have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Intentionally or not, the two movements have basically eliminated the PRS in urban China. In 1978, 72% of the urban households lived in public rental housing (Deng, et al, 2017). It was not until Deng Xiaoping came to power and adopted market-oriented economic measures that the PRS began to grow.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Intentionally or not, the two movements have basically eliminated the PRS in urban China. In 1978, 72% of the urban households lived in public rental housing (Deng, et al, 2017). It was not until Deng Xiaoping came to power and adopted market-oriented economic measures that the PRS began to grow.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Some studies also take the characteristics of destination cities into consideration. Due to the uneven patterns of urbanization and economic development in China, there are strong inter-city differences in terms of local resources, local institutional power and local welfare policies [6,31]. Liu, Deng and Song [22] studied migrants' settlement intentions in 282 Chinese cities, and found that regional differences and city characteristics had a significant impact on the settlement choices of migrants.…”
Section: Permanent Settlement and Hukou Transfer Intentions Of Migrantsmentioning
confidence: 99%
“…The exact package of welfare benefits that urban hukou holders enjoy depends on the city they live in [5]. In contrast, rural hukou holders are granted access to farmland and a homestead, but little else [6]. Given these differences between urban and rural hukou holders, the hukou system has become a tool for social welfare distribution, and the political, economic, and cultural dimensions of the urban-rural differences are deeply attached to one's hukou [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…For example, inequality can be created between a homeowner and a tenant (who does not accumulate housing assets) or between a homeowner living in a "good" location and another living in a deprived neighbourhood. Intergenerational transfers may also reproduce inequality in housing asset holding across generations (Deng et al, 2017).…”
Section: Asset-based Welfare In the Global Northmentioning
confidence: 99%